METTL3 as a potential therapeutic target in gastric cancer - Yu, Zhefei; Yang, Yang (Frontiers in Oncology, 2024)
Gastric cancer (GC) is one of the leading causes of cancer-related death worldwide. N6-methyladenosine (m6A) modification is the most prominent epigenetic modification of eukaryotic mRNAs, and methyltransferase-like 3 (METTL3), a core component of the methyltransferase complex, catalyzes m6A modification. The results of previous studies indicate that the expression level of METTL3 is significantly elevated in gastric cancer tissues and cells. In addition, fluctuations in m6A levels induced by METTL3 are closely associated with the malignant progression of tumors as well as the poor prognosis of patients with gastric cancer. In this review, we focus on the potential mechanism of METTL3 in gastric cancer, and through our analysis, we suggest that targeting METTL3 could be a new therapeutic tool for treating GC.